A combination of targeted toxin technology and the piggyBac‐mediated gene transfer system enables efficient isolation of stable transfectants in nonhuman mammalian cells. Issue 1 (5th December 2014) - Sato, Masahiro; Inada, Emi; Saitoh, Issei; Matsumoto, Yuko; Ohtsuka, Masato; Miura, Hiromi; Nakamura, Shingo; Sakurai, Takayuki; Watanabe, Satoshi
Abstract Isolation of cells harboring exogenous DNA is typically achieved by the introduction of plasmids, but its efficiency remains still low. In this study, we developed a novel strategy to obtain stable transfectants efficiently. Porcine embryonic fibroblasts were transfected with two plasmids: (i) pTransIEnd, which comprises the ubiquitous promoter, the piggyBac (PB) transposase gene, an internal ribosomal entry site, the Clostridium perfringens‐derived endo‐β‐galactosidase C (EndoGalC) gene, and a poly(A) tail and (ii) a PB‐based plasmid, termed pT‐EGFP, which contains enhanced green fluorescent protein (EGFP) expression unit flanked by PB acceptor sites. The PB transposase can accelerate the chromosomal integration of transposon vectors. EndoGalC expression results in removal of a cell surface α‐Gal epitope, which is specifically recognized by Bandeiraea simplicifolia isolectin‐B4 (IB4). Four days after transfection, cells were treated with IB4SAP (IB4 conjugated to saporin, which eliminates any α‐Gal epitope‐expressing cells) for a short period, followed by standard culture for approximately 10 days. Several colonies emerged, most of which were positive for EGFP expression and lacked TransIEnd. These results indicated that the proposed approach is useful and efficient for obtaining stable transfectants without the use of drug‐resistance genes, and offers a novel route for gene manipulation in cultured nonhuman mammalian cells.